Efficacy of Acupuncture for Parkinson's Disease over the Last Decade: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Yeonju Kim; Yigun Lim; Subin Ahn; Junyeop Oh; Yoonbyeong Chae; Yoomin Choi; Jong Uk Kim (MEDrang Inc., 2024)
The aim of this review is to consolidate findings from clinical investigations spanning the past decade regarding the impact of acupuncture on Parkinson's disease (PD). The objective is to assess the efficacy of acupuncture as a therapeutic approach to PD, with the intention of informing future clinical practices and advancing the foundation for subsequent research endeavors in this area. A comprehensive literature search was conducted to identify clinical trials exploring the effects of acupuncture on PD between January 2014 and August 2023. Databases search included PubMed, EMBASE, CNKI, OASIS, KISS, KMBASE, RISS, and ScienceON. Quantitative evidence from randomized controlled trials (RCTs) was systematically reviewed, and the methodological quality of the included studies was assessed using Cochrane's risk of bias tool. Meta-analysis was performed using Review Manager (RevMan) 5.4.1 software. The systematic review encompassed a total of 38 RCTs involving 2,786 participants. Meta-analysis of 12 studies revealed that individuals treated with a combination of acupuncture and Western medicine exhibited notable improvements compared to those receiving Western medicine alone or sham acupuncture alongside Western medicine. However, the overall quality of the RCTs was deemed low, and no serious adverse events were reported. Across clinical investigations conducted in the past decade, acupuncture appears to hold promise as a complementary treatment for PD patients when administered alongside Western medicine. Nevertheless, this study identifies certain limitations that warrant consideration in future research endeavors. Enhanced emphasis on conducting high-quality RCTs is imperative to comprehensively evaluate the efficacy of acupuncture in managing PD.